2014
DOI: 10.4102/phcfm.v6i1.665
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of non-occupational HIV post-exposure prophylaxis amongst first- and second-year medical students at Stellenbosch University in South Africa

Abstract: BackgroundHuman immunodeficiency virus (HIV) infection is a worldwide problem, with 68% of infected people residing in sub-Saharan Africa. Antiretroviral therapy is used as post-exposure prophylaxis (PEP) to prevent infection in cases of occupational exposure, and use has recently been expanded to non-occupational exposure. Studies have demonstrated a lack of awareness of non-occupational PEP (NO-PEP) in the general population.AimThe aim of this study was to evaluate knowledge and attitudes towards availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A study conducted among 400 participants who attended a clinic in Jerusalem for HIV testing reported lower awareness of PEP, with only 24% of participants being aware that the time window for effective PEP is 72 h [ 34 ]. In a South African study of 169 medical university students, only 28% reported that PEP can be used to prevent HIV infection [ 35 ]. Conversely, an American survey of 529 respondents in 2016–2017 reported a higher level of awareness, with 59% of participants being aware of PEP [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among 400 participants who attended a clinic in Jerusalem for HIV testing reported lower awareness of PEP, with only 24% of participants being aware that the time window for effective PEP is 72 h [ 34 ]. In a South African study of 169 medical university students, only 28% reported that PEP can be used to prevent HIV infection [ 35 ]. Conversely, an American survey of 529 respondents in 2016–2017 reported a higher level of awareness, with 59% of participants being aware of PEP [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As only a proportion of our Kenyan texts are from Western Kenya, it makes sense that VMMC should feature most prominently in the Swazi sample, though it is disappointing that it is mentioned in only one 2014 text. We have been unable to locate data on PEP coverage in SSA; Ncube et al [7] note that its availability is limited even in South Africa. PrEPWatch [30] reports the number of PrEP users per country.…”
Section: Plos Onementioning
confidence: 97%
“…Postexposure prophylaxis (PEP), the short-term use of antiretrovirals following exposure, has been acknowledged to reduce the risk of HIV infection since the early 1990s. Although PEP is acknowledged as an important intervention to prevent sexual transmission in SSA [6], its availability even in South Africa has been limited [7]. However, as a post-violence care intervention, it is currently a core component of the DREAMS (Determined, Resilient, Empowered, AIDS-free, Mentored and Safe) project to reduce HIV infections among AGYW in ten highly affected countries in SSA [8].…”
Section: Introductionmentioning
confidence: 99%
“…Theme 2: Attitudes towards PEP ( n = 4) (Bareki & Tenego 2018 ; McDowall & Laher 2019 ; Mekgoe et al 2019 ; Ncube et al 2014 ).…”
Section: Thematic Analysis Of Selected Studiesmentioning
confidence: 99%
“…Theme 3: Adherence towards and practice of PEP ( n = 10) (Aigbodion et al 2019 ; Bareki & Tenego 2018 ; Kabotho & Chives 2020 ; Mabina et al 2018 ; Makhado & Davhana-Maselesele 2016 ; Makhado & Seekane 2020 ; McDowall & Laher 2019 ; Mossburg et al 2019 ; Ncube et al 2014 ; Rasweswe & Peu 2020 , 2021).…”
Section: Thematic Analysis Of Selected Studiesmentioning
confidence: 99%